2013
DOI: 10.3109/17453674.2013.867781
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative corticosteroid injections are associated with worse long-term outcome of surgical carpal tunnel release

Abstract: Background and purposeFailed closed treatment of carpal tunnel syndrome (CTS) is often followed by surgery. We investigated whether preoperative steroid injections could have a negative effect on the long-term outcome of the operation.Patients and methods174 hands (164 patients) were operated on by a single surgeon at Tartu University Hospital in 2005. The patients were interviewed by telephone 5–6 years after the operation. Self-reported data were gathered retrospectively concerning the number of steroid inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…1 Although authors have suggested that a steroid injection reduces the need for further surgery, other studies have advocated for immediate surgical release as a more cost-effective treatment option. 5,23,26 Regardless, recent literature has shown that nationwide practice varies, as does the reported success rate of steroid injections, and that initial steroid injection may reduce the number of surgical releases eventually performed. 11,12,24 The purpose of this study is to use the previously described payer perspective to assess the relative costs of different treatment options: either immediate surgical release or up to 3 attempted injections.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although authors have suggested that a steroid injection reduces the need for further surgery, other studies have advocated for immediate surgical release as a more cost-effective treatment option. 5,23,26 Regardless, recent literature has shown that nationwide practice varies, as does the reported success rate of steroid injections, and that initial steroid injection may reduce the number of surgical releases eventually performed. 11,12,24 The purpose of this study is to use the previously described payer perspective to assess the relative costs of different treatment options: either immediate surgical release or up to 3 attempted injections.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, 1 study conducted in Estonia reported that patients who received repetitive steroid injections were more likely to have postoperative symptoms of carpal tunnel syndrome if they eventually opted for surgery. 14 Acupuncture is commonly used to manage pain and neuropathy in Chinese medicine. A systematic review published in 2011 included 2 trials that compared acupuncture and steroid injection; acupuncture was found to be slightly better in reducing symptoms of carpal tunnel syndrome.…”
mentioning
confidence: 99%
“…It did not however, affect overall patient satisfaction with the surgical outcome. This study is substantially larger than the 164 patients reported by Vahi et al (2014) and both initial patient variables and outcomes are documented using standard instruments.…”
Section: Discussionmentioning
confidence: 99%